2000
DOI: 10.1007/978-3-642-57297-5
|View full text |Cite
|
Sign up to set email alerts
|

Embryology of Dolphins

Abstract: The use of general descriptive names, registered names, trademarks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use.Product liability: The publishers cannot guarantee the accuracy of any information about dosage and application contained in this book. In every individual case the user must check such information by consulting the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…Another potential source of error in utilizing blubber progesterone levels to determine pregnancy, is the timing of the elevation and decline in blubber progesterone with respect to commencement and termination of pregnancy. In our study, we observed that in embryos with total lengths <1 cm or approximately 2–3 wk postconception (Šterba et al 2000), blubber progesterone levels were between 183 and 248 ng/g, well within the total range we see for females with larger fetuses and much higher than those found in non‐pregnant animals. This suggests that progesterone levels rise quickly in the blubber at the commencement of pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…Another potential source of error in utilizing blubber progesterone levels to determine pregnancy, is the timing of the elevation and decline in blubber progesterone with respect to commencement and termination of pregnancy. In our study, we observed that in embryos with total lengths <1 cm or approximately 2–3 wk postconception (Šterba et al 2000), blubber progesterone levels were between 183 and 248 ng/g, well within the total range we see for females with larger fetuses and much higher than those found in non‐pregnant animals. This suggests that progesterone levels rise quickly in the blubber at the commencement of pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…1). All of these features are obvious in our perinatal specimens and are characteristic for stage S 11 in the ontogenetic classification system of Štěrba et al (2000) but also for neonatal dolphins. In general, the head of the perinatal Pacific spotted dolphin is rather similar morphologically to that of the adult and reflects the precocial developmental state of these animals.…”
Section: Resultssupporting
confidence: 66%
“…Whereas cetacean embryos largely show plesiomorphic characters also seen in other mammals of the same developmental age (Oelschläger and Buhl, 1985a, b; Oelschläger et al, 1987; Buhl and Oelschläger, 1988; Oelschläger and Kemp, 1998; Klima, 1999; Štěrba et al, 2000; Richardson and Oelschläger, 2002), early fetal stages illustrate the transition from the eutherian bauplan to cetacean organization (e.g., the realization of an uncoupled ear complex and a beak‐like larynx; Fig. 10).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Early in development, the heads of cetacean embryos closely resemble those of other mammals at similar developmental stages, but they begin to acquire more typical cetacean shapes in the late embryonic and early fetal stages (Gill, ; Štěrba et al, ; Thewissen and Heyning, ; Roston et al, ). This observation is consistent with the finding that early stages of facial development are conserved throughout tetrapods (Young et al, ).…”
Section: Biology Of Telescoping: An Overviewmentioning
confidence: 99%